2017
DOI: 10.1016/j.omtn.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Fusion Genes in Pediatric Cancers: Toward Precision Medicine

Abstract: Pediatric cancers differ from adult tumors, especially by their very low mutational rate. Therefore, their etiology could be explained in part by other oncogenic mechanisms such as chromosomal rearrangements, supporting the possible implication of fusion genes in the development of pediatric cancers. Fusion genes result from chromosomal rearrangements leading to the juxtaposition of two genes. Consequently, an abnormal activation of one or both genes is observed. The detection of fusion genes has generated gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 139 publications
(106 reference statements)
1
59
0
Order By: Relevance
“…This is the largest molecular study involving sporadic pediatric PTC (up to 18 years old) ( to tumors without fusions. 49,50 Notably, AGK-BRAF fusion was significantly associated with the presence of distant metastasis, with the lung being the only metastatic site outside of the neck in this set of PTC samples.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is the largest molecular study involving sporadic pediatric PTC (up to 18 years old) ( to tumors without fusions. 49,50 Notably, AGK-BRAF fusion was significantly associated with the presence of distant metastasis, with the lung being the only metastatic site outside of the neck in this set of PTC samples.…”
Section: Discussionmentioning
confidence: 78%
“…These data are in agreement with the literature. It has been suggested that pediatric cancers usually harbor fewer mutations than adult cancers and that tumors with fusions have a much lower mutational burden compared to tumors without fusions …”
Section: Discussionmentioning
confidence: 99%
“…The detection of DNAJB1-PRKCA gene fusion in fibrolamellar hepatocellular carcinoma (FLHCC) serves as illustrative example for both the powerful detection at unprecedented resolution by RNA sequencing (RNA-seq) and its successful diagnostic use in extremely rare tumors. 6 Therefore, the discovery of additional actionable fusion transcripts in cancers is attracting more attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that pediatric cancers differ from those of adults, as many arise from embryonal rather than epithelial cells 13 and as they particularly harbor low mutation rates, mostly due to the lower implication of exogenous toxic effects. 6 The exploration of the fusion landscape in these pathologies could, therefore, help to unravel the particularity of these malignancies and provide new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…They occur when two genes become fused together due to chromosomal rearrangements and can result in inactivation of tumour suppressor genes and activation of proto-oncogenes. MYC is a proto-oncogene that exerts its effect by controlling multiple splicing factors 14. Cancers that overexpress MYC can be targeted by specific splice-modifying agents 15.…”
Section: How Is Transcriptomics Clinically Relevant?mentioning
confidence: 99%